Single domain intracellular antibodies: a minimal fragment for direct in vivo selection of antigen-specific intrabodies. - Tanaka, T; Lobato, M; Rabbitts, T (2003)
There is a major need in target validation and therapeutic applications for molecules that can interfere with protein function inside cells. Intracellular antibodies (intrabodies) can bind to specific targets in cells but isolation of intrabodies is currently difficult. Intrabodies are normally single chain Fv fragments comprising variable domains of the immunoglobulin heavy (VH) and light chains (VL). We now demonstrate that single VH domains have excellent intracellular properties of solubility, stability and expression within the cells of higher organisms and can exhibit specific antigen recognition in vivo. We have used this intracellular single variable domain (IDab) format, based on a previously characterised intrabody consensus scaffold, to generate diverse intrabody libraries for direct in vivo screening. IDabs were isolated using two distinct antigens and affinities of isolated IDabs ranged between 20 nM and 200 nM. Moreover, IDabs selected for binding to the RAS protein could inhibit RAS-dependent oncogenic transformation of NIH3T3 cells. The IDab format is therefore ideal for in vivo intrabody use. This approach to intrabodies obviates the need for phage antibody libraries, avoids the requirement for production of antigen in vitro and allows for direct selection of intrabodies in vivo.